The Influence Of Peer Group And Religius On Adolescent Delinquency In Students Of Madrasah Aliyah Alwashliyah Tebing Tinggi City - Andriati , Ayu; Darmayanti, Nefi; Fadillah , Risydah (International Journal of Educational Research & Social Sciences, 2024)
The occurrence of juvenile delinquency shows that teenagers are indisciplined towards the applicable rules and norms, be it family, school, society or their own norms as individuals. The phenomenon of juvenile delinquency seems to be a never-ending theme to be researched and discussed . The causes of juvenile delinquency include the result of wrong parenting patterns, a bad school environment, bad peers , a social and community environment that is not conducive, weak self-control, and emotional maturity in teenagers who do not develop according to the age level of development. teenagers and their lack of religious values. The aim of this research is to determine the influence of peers and religiosity on juvenile delinquency at MAS Al Washliyah, Tebing Tinggi City. This research was carried out at MAS Alwashliyah Tebing Tinggi. The research method uses quantitative research methods with a sample population of 217 students. The research results show that there is a significant influence between peers and religiosity and juvenile delinquency seen from the coefficient value (R²) = 0.181 with p = 0.000 < 0.050, meaning that the emergence of juvenile delinquent behavior is influenced by the influence of peers and the level of religiosity, with a contribution of 18.1%.